Examination of Anger Prevalence in NCAA Division I Student-Athletes - Madden, Robert; Winkelmann, Zachary; Weber, Samantha; Moore, Erin; Torres-McGehee, Toni (Bowling Green State University, 2021)
Purpose: Anger associated with sports participation may affect inability to acutely process anger, may decrease performance and increase the likelihood of risk-taking behavior in collegiate athletes. Therefore, the purpose was to examine the prevalence of anger in collegiate student-athletes across sex, academic status, and sport type. Methods: A cross sectional study over a three-year period examined 759 NCAA Division I student-athletes at one institution (age=20±1 years; males: n=259; females: n=500) completed an optional pre-participation behavioral health screening questionnaire, personal demographic information and the Anger Index Self-Test. Results: Overall, 37.2% (n=282/759; males=127/259, 49.0%; females=155/500, 31.0%) of participants were at high-risk for anger. We identified a significant difference between the anger and sex [Χ2(2, N=759) =28.1, P≤0.01]. We also identified a significant difference between the anger and sport type [Χ2(8, N=759)=32.1, P≤0.01] with 55.2% (n=419/759) at moderate risk for anger despite sport type; with the highest percentages presenting high-risk for anger within power sports (n= 64/116, 55.2%) and ball sports (n=98/240, 40.8%). No significant differences were identified for anger risk and academic status (P=0.66). Conclusions: Female collegiate student-athletes demonstrated a higher prevalence of anger than male collegiate student-athletes, yet more males were high-risk. Most student-athletes displayed moderate-risk for anger across different sports. Anger across academic status was not significantly different implying that anger management and coping skills may need to be taught during their student-athlete tenure to mitigate the identified risk. A collegiate student-athlete's inability to process anger may affect sports performance and have negative consequences on their personal and social life. A primary prevention mechanism exists to explore proper coping mechanisms for anger during sport before the onset of mental health conditions that could exacerbate the experience for the individual.